INFLUENCE OF LEARNING STYLE ON ACADEMIC ACHIEVEMENT OF PRIMARY SCHOOL STUDENTS - Mayong Mayong; Muhammad Alfian Tuflih (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the influence of learning styles on academic achievement of primary school students. Learning style is identified as each individual's unique way of receiving and processing information, which includes visual, auditorial and kinesthetic types. The results showed that there is a significant relationship between learning styles and students' academic outcomes. Students who learn with a visual style perform better when the material is presented in a visual format such as pictures and diagrams. Students with an auditorial learning style achieve more optimally through oral teaching methods and verbal interaction. Meanwhile, kinesthetic students attain higher academic achievement when engaged in physical activities and practical learning. The conclusion of this study confirms the importance of adapting teaching methods to suit students' learning styles to improve academic achievement and optimise their learning potential.